2021
DOI: 10.1002/fsn3.2440
|View full text |Cite
|
Sign up to set email alerts
|

Safety assessment of HEA‐enriched Cordyceps cicadae mycelia on the central nervous system (CNS), cardiovascular system, and respiratory system in ICR male mice

Abstract: Cordyceps cicadae, also known as the cicadae flower, is a wellknown entomopathogenic fungus. The C. cicadae mycelia are parasitic toward specific hosts, such as Cicada flammata Distant, Platypleura kaempferi Fabricius, Crytotympana pustulata Fabricious, Platylomia pieli Kato, and Oncotympana maculatieollis Motsch (Zeng et al., 2014). The cicadae flower has been used as traditional Chinese medicine (not only in China but also in Japan and Taiwan) for at least 1,600 years to treat fatigue, night perspiration, fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…This proved that HEA could pass through the blood–brain barrier (BBB). The CCME promptly initiated IOP reduction at 1 h following the oral route [ 19 ]. Studies on pharmacokinetics and blood–retina–barrier (BRB) are also needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This proved that HEA could pass through the blood–brain barrier (BBB). The CCME promptly initiated IOP reduction at 1 h following the oral route [ 19 ]. Studies on pharmacokinetics and blood–retina–barrier (BRB) are also needed.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with HEA (20 and 40 mg/kg) for six weeks reduced blood glucose in alloxan-induced diabetic rats [ 9 ]. The safety of C. cicadae mycelium has been evaluated in rat, rabbit, pig, and mouse models, as well as humans [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…O sinensis has multiple bioactivities, including those relating to antitumor, immune regulation, cardiovascular protection, treatment of diabetes, and anti-oxidation. [2][3][4][5][6][7] The cultured mycelium of O sinensis is regarded as a substitute for O sinensis and appears to have significant biological activity. Indeed, Wu et al found that sphingolipids isolated from the cultured mycelium of O sinensis demonstrated immunological activity by inhibiting the viability of mouse splenocytes, as well as that of splenocyte-derived B and T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous research into eye health has shown promising results, motivating us to investigate other important aspects that have yet to be studied. Specifically, we discovered that HEA was present in brain tissue, indicating that it was able to penetrate the blood–brain barrier [ 31 ]. This suggests that the compound may have potential in alleviating eye diseases, thus, helping to reduce the effects of eye disease and contributing to overall improvements in ocular health.…”
Section: Introductionmentioning
confidence: 99%